Innovation, firm productivity, and export survival: Firm-level evidence from ASEAN developing countries - Utumporn Jitsutthiphakorn (Journal of Economic Structures, 2021)
This firm-level study investigates the importance of innovation as a determinant of firm productivity and how firm productivity could impact firm export survival. This is the first integration of the innovation approach, productivity approach, and firm survival approach to explore their linkages at the regional level in ASEAN developing countries. Using the panel database from the World Bank Enterprise Survey, which covers six developing countries in ASEAN - the Philippines, Indonesia, Vietnam, Laos, Cambodia, and Myanmar - and also covers six selected industries, we construct four equations: innovation inputs, innovation output, firm productivity, and export survival. The four equations' findings suggest that the technology level of the sector, firm size, and exports are significant factors for R&D expenditure (innovation input). R&D expenditure is a significant driver of a firm's product and process innovation (innovation output). Increasing firm productivity in the six ASEAN developing countries we considered is driven by process innovation rather than product innovation, and productive firms are more likely to survive in the export market.
Keywords: D24; F14; F23; O31; 330; ASEAN; Export survival; Firm productivity; Firm survey; Innovation